Individual behavioral profiling as a translational approach to assess treatment efficacy in an animal model of post-traumatic stress disorder - Sarkar, Ishita; Snippe-Strauss, Maja; Tenenhaus Zamir, Adi; Benhos, Amir; Richter-Levin, Gal (Frontiers in Neuroscience, 2022)
A major challenge in treating post-traumatic stress disorder (PTSD) continues to be the large variability in responsiveness to pharmacotherapy. Only 20–30% of patients experience total remission to a specific treatment, while others demonstrate either partial remission or no response. However, this heterogeneity in response to pharmacotherapy has not been adequately addressed in animal models, since these analyze the averaged group effects, ignoring the individual variability to treatment response, which seriously compromises the translation power of such models. Here we examined the possibility of employing an “individual behavioral profiling” approach, originally developed to differentiate between “affected” and “exposed-unaffected” individuals in an animal model of PTSD, to also enable dissociating “responders” or “non-responders” after SSRI (fluoxetine) treatment. Importantly, this approach does not rely on a group averaged response to a single behavioral parameter, but considers a cluster of behavioral parameters, to individually characterize an animal as either “responder” or “non-responder” to the treatment. The main variable to assess drug efficacy thus being the proportion of “responders” following treatment. Alteration in excitatory/inhibitory (E/I) balance has been proposed as being associated with stress-related psychopathology. Toward a functional proof of concept for our behaviorally-based characterization approach, we examined the expression patterns of α1 and α2 subunits of GABAA receptor, and GluN1 and GluN2A subunits of the NMDAR receptor in the ventral hippocampus, as well as electrophysiologically local circuit activity in the dorsal dentate gyrus (DG). We demonstrate that with both parameters, treatment “responders” differed from treatment “non-responders,” confirming the functional validity of the behavior-based categorization. The results suggest that the ability to respond to fluoxetine treatment may be linked to the ability to modulate excitation-inhibition balance in the hippocampus. We propose that employing the “individual behavioral profiling” approach, and the resultant novel variable of the proportion of “recovered” individuals following treatment, offers an effective translational tool to assess pharmacotherapy treatment efficacy in animal models of stress and trauma-related psychopathology.